The Impact of Game-Based Learning on Computational Thinking and Language Learning Attitudes in Higher Education Students - Al Mahrouqi, Raya Saleem; Khodabandelou, Rouhollah; Osman, Mohamed Eltahir (Journal of Ecohumanism, 2024)
Computational thinking (CT) is recognized as a fundamental skill in the 21st century, potentially improving problem-solving and creative thinking abilities. Given its broad applicability, there is a growing emphasis on introducing CT in education. Additionally, Oman Vision 2040 underscores the importance of advancing education and nurturing a highly skilled workforce, emphasizing the need for computational thinking, problem-solving, critical thinking, and algorithmic reasoning skills. Thus, since previous research has primarily focused on middle and high school students, and the studies for higher education showed that students lack CT competencies, this study extends the investigation to higher education students. Moreover, integrating CT into the curriculum calls for innovative teaching methods, such as game-based learning, which promises to engage students in complex activities closely aligned with CT principles. This research endeavors to investigate the impact of game-based learning on the CT skills and attitudes towards language learning of higher education students with consideration of potential gender-based differences. The problem statement highlights CT's significance and the pressing need for improved CT competencies among students. A comprehensive methodology employed a quasi-experimental design, encompassing pre-and post-tests, interviews, and questionnaires, to gather data from 24 Sultan Qaboos University Foundation students. The findings showed a considerable positive impact on students’ CT skills as well as their language learning attitudes. In light of the research findings, it is recommended that game-based learning be incorporated into higher education curricula to enhance CT skills and engagement.